1991
DOI: 10.1128/iai.59.12.4590-4598.1991
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of Escherichia coli endotoxin in vivo primes in vitro superoxide anion release in rat polymorphonuclear leukocytes and Kupffer cells in a time-dependent manner

Abstract: Continuous infusion of a nonlethal dose of Escherichia coli lipopolysaccharide (LPS) (0.5 mg/kg) in#dced early (3 h) accumulation of polymorphonuclear leukocytes (PMNL) in rat liver followed by later (30 h) greater extravasation of mononuclear phagocytes (MNP) (E. B. Rodriguez de Turco and J. A. Spitzer, J. Leukocyte Biol. 48:488-494, 1990). Nonparenchymal liver cells from rats treated for 3 and 30 h with LPS were recovered by centrifugal elutriation, yielding a 23-ml/min fraction (endothelial cells) and a 45-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…They may also be effector cells for immune responses; they present different surface antigens (37 ). We demonstrated earlier that participation of these cells in superoxide production after i n uiuo ET exposure and in response to stimulation by various agents i n uitro is far less than that by Kupffer cells or liver-sequestered neutrophils ( 19). In a later publication McCloskey et al (38) also demonstrated in a different endotoxic model the substantial quantitative difference in superoxide anion production between hepatic macrophages and endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They may also be effector cells for immune responses; they present different surface antigens (37 ). We demonstrated earlier that participation of these cells in superoxide production after i n uiuo ET exposure and in response to stimulation by various agents i n uitro is far less than that by Kupffer cells or liver-sequestered neutrophils ( 19). In a later publication McCloskey et al (38) also demonstrated in a different endotoxic model the substantial quantitative difference in superoxide anion production between hepatic macrophages and endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…The nonparenchymal sinusoidal cells of the liver includein addition to Kupffer cellsendothelial, Ito and pit cells. Previously we demonstrated phorbol myristate acetate (PMA)-stimulated superoxide anion release by hepatic endothelial cells of continuously endotoxemic rats to a much smaller extent than that by Kupffer cells and liver infiltrated polymorphonuclear cells from such animal models (19). In Figure 6 evidence is presented for NO production by hepatic endothelial cells of saline solution-and ET-infused rats in the absence and presence of ET, TNF, IL-1p and various combinations of these agents.…”
Section: Stimulation Of No Formation By Et and Various Cytokines In Hmentioning
confidence: 91%
“…Previous investigators have noted that O 2 Ϫ release from rat PMNs appears to be a fraction of that produced by human PMNs. However, the majority of previously published work on rat PMNs has been performed on elicited PMNs [5,9,11,[26][27][28], which may be functionally different from quiescent PMNs. We hypothesized that this disparity in measured O 2 Ϫ formation is because the rat PMN preferentially releases other oxidant species during the respiratory burst and we sought to test this hypothesis in the quiescent, circulating rat neutrophil.…”
Section: Discussionmentioning
confidence: 99%
“…In efforts to elucidate the mechanisms of ROS-mediated PMN cytotoxicity and, indeed, to develop effective therapeutic strategies, many productive animal models of inflammatory states have been developed. ROS-mediated tissue injury by PMNs has been implicated in models of ARDS [3], ischemia/ reperfusion [4], and sepsis [5] through the use of appropriate analogs. As with any animal model, however, species differences may limit the conclusions that can be reasonably reached.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue injury during endotoxemia is often attributed to PMN-derived reactive oxygen species (ROS), and treatment with antioxidants or blocking PMN function can prevent endotoxemia-related pulmonary injuries [42]. Some studies suggest that adhered or tissue-associated PMNs demonstrate even greater oxidant potential than circulating PMNs during endotoxemia [4,43,44]. However, instances of depressed or unaltered oxidant production by PMNs during endotoxemia are also reported [45][46][47].…”
Section: Oxidant Productionmentioning
confidence: 99%